Action movement for the environment through plastic waste management in Suka Makmur Village, Binjai District, Langkat Regency - Khairani, Leylia; Sima, Hafazira; Santoso, Puji (Community Empowerment, 2021)
Public awareness regarding the environment that comes from waste management still requires special attention. Garbage is often an environmental problem not only in urban areas, but also in rural areas. Therefore, it is necessary to carry out mentoring activities in the form of intense socialization to increase understanding of waste management and utilization from various parties, including universities. The Action Movement for the Environment (GAUL) was one of the programs that aims to increase citizen understanding in waste management, and also involve the community directly in managing waste that can be recycled (re-use). Through the methods of observation, socialization, and participatory action, it is able to raise awareness and increase citizen understanding.